ANALISIS FERTILITAS PADA WANITA BEKERJA DI KOTA PALANGKA RAYA - Yudi Pungan (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2016)
Relatedness of opinion on fertility is when there is an increase on one’s income, this will provide greater effect on the decrease of fertility. This research aims to know and describe the effects of income, cost of children, working hours, age of first marriage, education and work location on working female fertility in Palangka Raya City. In this paper, the data collection technique is by Library Research), namely the data collection technique through various literatures to obtain theoretical basic equipment such as books, magazines, bulletins as well as other relevant readings to the studied issues. (b) Field Research, namely by direct observation on the observed objects.The research result of independent variable effect results on dependent variables in a whole can be seen from the value of F-Count by 17,954 with the probability level of 0,000 (significance). Because the probability is much smaller than α = 0,05, so the regression model can be used to predict the affecting factors on fertility on working female in palangka Raya city in terms of poor family or can be said that income, cost of children, working hours, age of first marriage, education and work location simultaneously affect significantly on fertility on working female in Palangka Raya city in poor family.